2017
DOI: 10.1177/0271678x17692815
|View full text |Cite
|
Sign up to set email alerts
|

Sequential PET estimation of cerebral oxygen metabolism with spontaneous respiration of 15O-gas in mice with bilateral common carotid artery stenosis

Abstract: 15 O-gas with isoflurane was supplied to the nose of mouse with evacuation of excess 15 O-gas surrounding the body. 15 O-PET was performed on days 3, 7, 14, 21, and 28 after surgery. Cerebral blood flow (CBF), cerebral blood volume, oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO 2 ) were calculated in whole brains. A significant decrease in CBF and compensatory increase in OEF in the BCAS group produced CMRO 2 values comparable to that of the sham group at three days post-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(60 reference statements)
0
11
1
Order By: Relevance
“…This is comparable to the results of a recent study using positron emission tomography (PET), in which the CBF in mice under 1.5% isoflurane anesthesia was found to be 0.62 ± 0.05 ml/g/min. 32 However, the CBF values in anesthetized mice in both studies were slightly higher than that reported for awake mice using the autoradiographic method, which was 0.5 ml/g/min. 33 It is likely that the anesthetic (isoflurane) contributed to the slightly higher CBF reported in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…This is comparable to the results of a recent study using positron emission tomography (PET), in which the CBF in mice under 1.5% isoflurane anesthesia was found to be 0.62 ± 0.05 ml/g/min. 32 However, the CBF values in anesthetized mice in both studies were slightly higher than that reported for awake mice using the autoradiographic method, which was 0.5 ml/g/min. 33 It is likely that the anesthetic (isoflurane) contributed to the slightly higher CBF reported in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Positron emission tomography (PET) with 15 O is considered the gold standard for the whole-brain oxygenation measurement in clinical setting [ 8 ]. While the method has been applied to mice [ 9 ], the method suffers from low spatial resolution which limits its usefulness for studying small species Moreover, the short half-life of [ 15 O] requires an on-site cyclotron, which restricts the widespread use of this approach. Alternatively, MRI-based techniques such as blood oxygenation level-dependent (BOLD), quantitative BOLD, susceptometry, T 2 -relaxation-under-spin-tagging and 17 O MR spectroscopy among others have been proposed for mapping oxygenation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, few [ 15 O]H 2 O PET studies have been conducted to evaluate cerebral blood flow and other haemodynamics in small animals primarily due to the short half-life of 15 O and its potentially high-energy emitted positron, which render the PET images noisier and of lower resolution. Nevertheless, the development of [ 15 O]H 2 O-based imaging in small animals is an increasing focus of recent research, and the aforementioned challenges may be technically addressed in the near future (more information is available on the website of the project Small Animal Fast MRI Insert at https://safir.ethz.ch) [43, 79–82].…”
Section: Discussionmentioning
confidence: 99%